2021
DOI: 10.3389/fgene.2021.624290
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Functions of MeCP2 in Rett Syndrome Pathology

Abstract: MeCP2 protein, encoded by the MECP2 gene, binds to DNA and affects transcription. Outside of this activity the true range of MeCP2 function is still not entirely clear. As MECP2 gene mutations cause the neurodevelopmental disorder Rett syndrome in 1 in 10,000 female births, much of what is known about the biologic function of MeCP2 comes from studying human cell culture models and rodent models with Mecp2 gene mutations. In this review, the full scope of MeCP2 research available in the NIH Pubmed (https://pubm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 142 publications
(214 reference statements)
0
16
0
Order By: Relevance
“…24 It has been reported that MECP2 plays a pivotal role in Rett syndrome pathology and a novel double mutation that can affect the transcription repression domain of MECP2 and cause a severe phenotype of Rett syndrome. [25][26][27] The results of our study reported here show that MECP2, the target of miR-205 in tenocytes was identified as an important transcriptional inhibitor, which might be a novel critical factor in the proliferation, migration and fibrosis of tenocytes.…”
Section: Discussionmentioning
confidence: 60%
“…24 It has been reported that MECP2 plays a pivotal role in Rett syndrome pathology and a novel double mutation that can affect the transcription repression domain of MECP2 and cause a severe phenotype of Rett syndrome. [25][26][27] The results of our study reported here show that MECP2, the target of miR-205 in tenocytes was identified as an important transcriptional inhibitor, which might be a novel critical factor in the proliferation, migration and fibrosis of tenocytes.…”
Section: Discussionmentioning
confidence: 60%
“…3). The dependence of these phases of response of W to PSI on the dual regulation of bdnf by MeCP2 suggests that the special MeCP2 binding kinetics may provide a possible explanation of complex effects of MeCP2 on gene expression [28-29, 48] and a potential therapeutic target for rescuing memory impaired by disruptions.…”
Section: Discussionmentioning
confidence: 99%
“…1). The effects of MeCP2 on gene expression are complex [2829]. MeCP2 can act as a repressor or activator of BDNF transcription depending on context.…”
Section: Methods: Model Developmentmentioning
confidence: 99%
“…Thus, we included a BDNF-CaMKIIα-BDNF positive feedback loop (Fig 1A . The effects of MeCP2 on gene expression are complex [28,29]. MeCP2 can act as a repressor or activator of BDNF transcription depending on context.…”
Section: Introductionmentioning
confidence: 99%